1986
DOI: 10.1128/iai.52.2.414-420.1986
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane protein profiles of Haemophilus pleuropneumoniae

Abstract: Outer membrane protein profiles of Haemophilus pleuropneumoniae were examined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Cells were disrupted by sonication, and outer membrane-enriched fractions were prepared by differential centrifugation and selective solubilization of the inner membrane with sodium N-lauroyl sarcosinate. Colony type, growth medium, time of harvest, and in vitro or in vivo passage had no appreciable effect on the protein profiles of the strains examined. Seven patterns wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
1

Year Published

1990
1990
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
7
39
1
Order By: Relevance
“…SDS-PAGE analysis of the OMP preparations from serotypes 1, 5, and 7 were consistent with those reported by Rapp et al (32) and Rycroft and Taylor (37). We have confirmed previous findings (33) that A. pleuropneumoniae OMP provided some protection against pleuropneumonia in pigs; however, it appeared to be less effective than the CE.…”
Section: Resultssupporting
confidence: 90%
“…SDS-PAGE analysis of the OMP preparations from serotypes 1, 5, and 7 were consistent with those reported by Rapp et al (32) and Rycroft and Taylor (37). We have confirmed previous findings (33) that A. pleuropneumoniae OMP provided some protection against pleuropneumonia in pigs; however, it appeared to be less effective than the CE.…”
Section: Resultssupporting
confidence: 90%
“…Additional serovar‐independent, outer membrane protein (OMP) antigens are present in A. pleuropneumoniae . Major OMPs of varying seroreactivity and approximately 39 to 44 kDa in size are shared among several serovars, 12,13 although studies at our laboratory have demonstrated an immunodominant, surface accessible 39‐kDa OMP is seroreactive and shared among all A. pleuropneumoniae serovars 14–17 . Because similar OMPs may exist among related pig pathogens, including Pasteurella multocida 18,19 and Haemophilus parasuis , 20 and antisera to these may be cross‐reactive with a 40‐kDa OMP of A. pleuropneumoniae , 20 evaluation of the diagnostic test specificity of the 39‐kDa ELISA antigen was considered important.…”
mentioning
confidence: 84%
“…Equal number of E. faecalis cells (10 9 cells mL )1 ) subjected to PDT as in previous experiments were collected by centrifugation. The outer membrane proteins were isolated as detailed elsewhere (20). Briefly, the cells collected were suspended in HEPES buffer (pH 7.4) and cells were disrupted with a sonicator at 15 kHz output (Sonoplus, Bandelin, Germany).…”
Section: Methodsmentioning
confidence: 99%